Rational design of a serum‐free culture medium for the growth of human myoblasts destined to cell therapy. (20th August 2016) - Parent, Victor A.; Tremblay, Jacques P.; Garnier, Alain
Abstract: Cellular therapy of Duchenne muscular dystrophy is currently showing encouraging results. However, there is still no serum‐free medium that allows multiplying functional myoblasts, the cells required for this therapy, obtained from healthy donors, in sufficient number. A systematic screen for a defined culture medium that would allow expanding fully functional human myoblasts at the same rate and to the same extent as the existing serum‐containing medium has been undertaken. To this end, 6 basal media and more than 60 defined additives have been screened for their individual as well as synergistic effects. The medium developed in this study permits a 12‐log expansion of human myoblasts over a 60‐day period. The cells obtained have the same capacity to fuse and form myofibres as myoblasts multiplied in serum‐containing medium.